Design Thinking-Based UI/UX for a Clean Water Education App: Perancangan UI/UX Aplikasi Edukasi Air Bersih Berbasis Metode Design Thinking - Adriano Putra Imanuel Posumah; Rangian Elroi Johanes; Victor Obetnego Johanes Senduk; Yosua Jackvin Kumontoy; Virginia Tulenan; Ade Yusupa (Universitas Sam Ratulangi, 2026)
Abstract — Clean water is a fundamental necessity for human health and survival, yet public awareness of the importance of sustainable water resource management remains relatively low. Limited understanding of environmental pollution and efficient daily water usage presents a major challenge that requires effective educational solutions. This study aims to design UI/UX of a mobile-based clean water education application as an interactive learning medium to enhance public awareness. A comprehensive Design Thinking approach comprising the empathize, define, ideate, prototype, and test stages was employed to ensure that the proposed design is user-centered. A high-fidelity prototype was developed using Figma and evaluated by 20 participants through task-based usability testing and the System Usability Scale (SUS) questionnaire. The evaluation results indicate that the application achieved an average SUS score of 81.25, placing it in the Acceptable category and corresponding to an acceptance grade of A. These findings demonstrate that a user-centered design approach is effective in creating an intuitive and easy-to-use interface, with strong potential to improve public literacy regarding clean water management. Key words— Clean Water; Design Thinking; Digital Education; System Usability Scale; UI/UX Abstrak —Air bersih merupakan kebutuhan fundamental bagi keberlangsungan hidup dan kesehatan manusia, namun tingkat kesadaran masyarakat terhadap urgensi pengelolaan sumber daya air yang berkelanjutan masih tergolong rendah. Kurangnya pemahaman mengenai dampak pencemaran lingkungan dan efisiensi penggunaan air sehari-hari menjadi tantangan utama yang memerlukan solusi edukatif. Penelitian ini bertujuan untuk merancang UI/UX aplikasi edukasi air bersih berbasis mobile sebagai media pembelajaran interaktif guna meningkatkan kesadaran masyarakat. Penelitian ini menerapkan metode Design Thinking secara komprehensif yang meliputi tahapan empathize, define, ideate, prototype, dan test untuk memastikan solusi desain berpusat pada kebutuhan pengguna. Prototipe high-fidelity dikembangkan menggunakan perangkat lunak Figma dan dievaluasi oleh 20 partisipan melalui pengujian kegunaan berbasis tugas serta kuesioner System Usability Scale (SUS). Hasil pengujian menunjukkan bahwa aplikasi memperoleh skor SUS rata-rata sebesar 81,25, yang menempatkannya dalam kategori Acceptable dengan skala penerimaan Grade A. Temuan ini membuktikan bahwa pendekatan desain berbasis pengguna efektif menciptakan antarmuka yang intuitif, mudah digunakan, serta berpotensi kuat dalam meningkatkan literasi masyarakat mengenai pengelolaan air bersih. Kata kunci — Air Bersih; Design Thinking; Edukasi Digital; System Usability Scale; UI/UX